Reproduction is costly in an infected aquatic insect. Issue 1 (2nd January 2017) - Krams, I.A.; Krama, T.; Trakimas, G.; Kaasik, A.; Rantala, M.J.; Škute, A.
Abstract : Internal energy reserves of animals are limited, and the current investment in reproduction often decreases survival or future reproductive success. Some studies showed that copulatory activities impair the strength of immune function in insects, while the recent evidence is contradictory. In this study we tested whether copulatory activity affects the rate of encapsulation response in males of Calopteryx splendens damselfly in allopatric populations, and in sympatric populations where C. splendens stay together with their superior competitor C. virgo . We also counted the number of eugregarines, which are common parasites of damselflies. Copulation activity did not affect the immunity of C. splendens males in allopatric populations. In sympatric populations C. splendens males had more gut parasites, and we found a significant interaction between parasite number and copulatory activity on the rate of encapsulation. Our results suggest that the costs of reproduction are higher in infected males, which may affect reproductive investment and sexual selection.